2012
DOI: 10.1186/1758-3284-4-15
|View full text |Cite|
|
Sign up to set email alerts
|

The cost burden of oral, oral pharyngeal, and salivary gland cancers in three groups: commercial insurance, medicare, and medicaid

Abstract: BackgroundHead and neck cancers are of particular interest to health care providers, their patients, and those paying for health care services, because they have a high morbidity, they are extremely expensive to treat, and of the survivors only 48% return to work. Consequently the economic burden of oral cavity, oral pharyngeal, and salivary gland cancer (OC/OP/SG) must be understood. The cost of these cancers in the U.S. has not been investigated.MethodsA retrospective analysis of administrative claims data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
150
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(164 citation statements)
references
References 19 publications
10
150
1
3
Order By: Relevance
“…7 A recent study examining the cost burden of oral, oropharyngeal, and salivary gland cancers found it to be higher for these head and neck cancers than most other types of cancer. 4 The healthcare cost expenditure for post-surgical head and neck cancer patients nearly triples after their index diagnosis. 8 With the care of head and neck cancer patients already being more expensive than the care of most other cancers, 4 consideration of cost should increasingly play a role in deciding among treatments of comparative effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 A recent study examining the cost burden of oral, oropharyngeal, and salivary gland cancers found it to be higher for these head and neck cancers than most other types of cancer. 4 The healthcare cost expenditure for post-surgical head and neck cancer patients nearly triples after their index diagnosis. 8 With the care of head and neck cancer patients already being more expensive than the care of most other cancers, 4 consideration of cost should increasingly play a role in deciding among treatments of comparative effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used insurance claims data to identify costs, 4,8,9 focusing either on disease type 4,9 or treatment type. 8 While having the advantage of determining actual cost, relying on claims coding to identify patients and treatments is not without fault; 24.5% to 67.1% of patients identified by a diagnosis of cancer had no consequent identifiable treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of OSCC and OPC continue to be diagnosed at an advanced stage, resulting in the need for more complex and more costly therapy and ultimately compromising favorable outcomes. 7,8 Premalignant, potentially detectable lesions are expected in the majority of OSCC, but it is not known if OPC arises from potentially clinically detectable precursor lesions. It is anticipated that increasing early detection and management of OPMD and early-stage SCC will lead to improved outcomes.…”
mentioning
confidence: 99%
“…Additionally, urgent and emergent dental needs may be managed when the patient is best able to tolerate the treatment, provided at a time of lowest risk to the patient or with appropriate medical support, to facilitate best outcomes which may reduce the need for additional hospitalization and intensive medical care that may impact survival and increase economic burden of treatment [9,18,19,28,60,61]. Therefore, oral and dental care before, during, and following cancer therapy are an important part of cancer treatment [7] and are best provided by educated and experienced dental providers, with good communication with the oncology team [47].…”
Section: Cancer Survivorsmentioning
confidence: 99%